Efforts to Improve Learning Outcomes Using Pop-Up Book Media in The Pancasila Education Subject - Manurung, Ria Anjelina; Maisyarah, Putri Ammy; Harianty, Shofya Sri (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine Efforts to Improve Learning Outcomes Using Pop-Up Book Media in Pancasila Education Subjects at Sd Negeri 066055 Medan Denai. The type of research used by the researcher is classroom action research. Classroom action research is research conducted by teachers in their own classes through self-reflection with the aim of improving their performance so that student learning outcomes increase. The location of this research is at Sd Negeri 066055 with the address Jalan Kasuari, Medan Denai. The implementation of this research was carried out on April 15, 2025 and May 5, 2025. The subjects in this study were students who were in the second grade of elementary school with a total of 15 students, consisting of 8 male students and 7 female students. The object of this research is the effort to improve learning outcomes using pop-up book media in Pancasila learning at SD Negeri 066055 Medan Denai. Based on the results of the research analysis that have been described in chapter IV, the results of the initial value of students before the application of pop-up book media were 65.6 in cycle I. Furthermore, the value of student learning outcomes after the application of pop-up book media was 81.8 in cycle II. Which means that in this study there has been an increase in learning outcomes using pop-up book media with the results of the initial value of 65.6 to 81.8. So it can be concluded that there is an increase in learning outcomes by using pop-up book media in Pancasila learning at SD Negeri 066055 Medan Denai.